Carbonate or ether based electrolyte for Li-Se batteries: An in-situ study of intermediate polyselenide formation - Mutlu, Tutku; Demir-Cakan, Rezan (Pergamon-Elsevier Science Ltd, 2021)
Li-Se batteries have recently been concidered as one of the most promising battery systems to satisfy the future energy storage needs. On the other hand, in order to further improve the electrochemical cell per-formances, understanding of the Li-Se cell working mechanism, especially focusing on the formation of dissolved Li polyselenides, is essential. In this work, an in-situ study of intermediate polyselenide forma-tion based on the 4-electrode cycling voltammetry (CV) and 3-electrode electrochemical impedance spec-troscopy (EIS) are used to detect the existence of polyselenides in carbonate and ether-based electrolytes. CV measurements reveal the presence of dissolved polyselenide intermediate formations in ether-based solvent while no signatures are observed in carbonate-based electrolytes. Similar findings are also ob-served by EIS measurements as well as investigating the self-discharge behavior. Therefore, these two electrochemical characterizations can be easily implemented as prompt and cost-effective techniques to investigate the impact of the electrolyte solvents. Contrary to the Li-S counterparts, the outcome of the work suggests that carbonate-based electrolytes can be simply employed in the field of Li-Se batteries. (c) 2021 Elsevier Ltd. All rights reserved.
Keywords: Li-Se batteries; Ether-based electrolytes; Carbonate-based electrolytes; Polyselenides dissolution; Electrochemical techniques